Changes in weight and body composition after initiating insulin therapy and their relationship with metabolic control during the first year of type 1 diabetes in adults. InLipoDiab1 Study - Miętkiewska, Maja; Uruska, Aleksandra (Journal of Medical Science, 2021)
Introduction. As in the general population, an increase in the incidence of overweight has been observed in individuals with type 1 diabetes (T1DM). Nevertheless, weight gain in this group may contribute to the deterioration of the metabolic management. The aim of this study was to evaluate changes in the body weight and body composition after initiating insulin therapy and to assess their relationship with the metabolic management during the first year of T1DM in adults. Material and Methods. The prospective analysis included 139 adults patients with newly diagnosed T1DM, treated with Intensive functional insulin therapy (IFI) from the onset of the disease (age 26.3 ± 5.9 years). Patients were assessed at the time of the diagnosis and after 12 months. Metabolic parameters, including the HbA1c and lipid profile were investigated. The group was divided according to weight gain during the follow-up period. Results. Weight gain was observed in 68.3% of participants (n = 95). In most cases an increase in body fat was found (41% vs 59% p = 0.01). Changes in the body weight corresponded to significant changes in body composition. Conversely, HbA1c decreased during the follow-up in all groups. The highest reduction was observed in a group with “excessive weight gain”. Additionally, a significant increase in high density lipoproteins was observed in each group. However, weight gain was not accompanied by a deterioration of the lipid profile. Conclusions. Weight gain is a considerable problem among adults with newly diagnosed T1DM and is connected mainly with an increase of adipose tissue above the normal range. Changes in the body weight, associated with body composition changes, did not result in the dysfunctions of the metabolic management.